THE USE OF PLOTAGON AS A CREATIVE DIGITAL MEDIA ING ENGLISH LANGUAGE TEACHING - Justsinta Sindi Alivi (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2024)
This paper presents some alternative activities using Plotagon as media to teach English skills in English language teaching (ELT) contexts. Plotagon is a video creator application allowing users to make interactive and attractive video materials in the form of storytelling animation.This paper particularly offers how to use Plotagon to make teaching and activities are more interactive in and beyond the classroom. Furthermore, Plotagon is potential to enhance not only teachers but also students’ creativity. The substitution augmentation modification redefinition (SAMR) model is also applied to describe how Plotagon is used in different levels of teaching and learning activities. Thus, this paper is expected to contribute practically to the teachers’ development and innovation especially in English language teaching contexts.